Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1002/jctb.506
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon surface modifications by adsorption of bacteria and their effect on aqueous lead adsorption

Abstract: The adsorption of Escherichia coli on different activated carbons has been studied. The activated carbon samples used have been characterized, determining their surface area, pore size distribution, elemental analysis, mineral matter analysis and pH of the point of zero charge. The adsorption capacity of these carbons increased with their hydrophobicity and macropore volume. The number of bacteria adsorbed on the demineralized activated carbon in a solution of pH value equal to the iso-electric point of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(201 citation statements)
references
References 34 publications
4
194
1
2
Order By: Relevance
“…The influence of interaction of oriented water dipoles and adsorbate molecules on the mechanism of adsorption was developed by Bockris et al [9,10]. The electrochemical theory is still used today for adsorption studies on activated carbons [7,11,12] development of new electrosorption processes on activated carbon [13] and other porous carbon materials [14].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of interaction of oriented water dipoles and adsorbate molecules on the mechanism of adsorption was developed by Bockris et al [9,10]. The electrochemical theory is still used today for adsorption studies on activated carbons [7,11,12] development of new electrosorption processes on activated carbon [13] and other porous carbon materials [14].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of bacterial adsorption onto the surface of nanostructures has been presented, e.g., in the work of Kang et al (2007) and Singh et al (2011). Similarly, the ability to create a biofilm and the adsorption of bacterial cells onto the surface of mineral materials, including carbon materials and modified clay minerals, were also demonstrated (Yee et al, 2000;Rivera-Utrilla et al, 2001;Yamamoto et al, 2001;Jiang et al, 2007;Rong et al, 2008). These studies also indicated the important roles of pH and the ionic strength of the solution as significant factors affecting the adsorption of bacterial cells onto the surface of minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these studies are also related to the adsorption of bacteria onto the surface of such materials. This is an important aspect of the research that involves the potential applications of these methods for microbiological water treatment (Rivera-Utrilla et al, 2001;Savage and Diallo, 2005;Li et al, 2008;Qu et al, 2013;Hossain et al, 2014). Similar investigations have focused not only on…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps this may be due to formation of hydroxides of these metal ions. The zero point charge pH ZPC of the pea peels was determined to explain the effect of pH on sorption process of Pb II and Ni II in aqueous solution 21 . It has been given in the literature that favorable pH for adsorption of cation is greater than that of pH ZPC while …”
Section: Effect Of Phmentioning
confidence: 99%